Coordination between loss of excitation protection and minimum excitation limit function of voltage regulation system: Coordination between relay protections and cabability curve - Vučićević, Darko; Buha, Danilo; Marinković, Savo; Gligorov, Saša; Malešević, Nevena (Proceedings, Electrical engineering institute "Nikola Tesla", 2021)
Established practice is such that the relay protection system and excitation system adjust independently of each other, which very often leads to incoordination action. When network disturbance occur, it is necessary to provide that basic protection functions eliminate the fault if necessary, and that all generators respond so as to preserve system stability and use their capabilities. The basic task of under excitation protection is to prevent damage to the machine in a permanently not allowed mode of operation and to prevent the absorption of large amounts of reactive power from system that can lead to voltage collapse or line failure in the transmission system. This paper deals with under excitation protection and minimal excitation limiter, which is a part of automatic voltage regulation of excitation system, as well as with coordination between them. In the paper current and proposed settings are presented whereby generators in power plants in „EPS” are taken into consideration.